Implementation of Waste Management Program: Case Study of Self–Government Unit of Bački Petrovac in Serbia - Valenćiková Marina (EU agrarian Law)
As part of the negotiations for EU accession, the Republic of Serbia through Chapter 27 (Poglavlje 27 u Srbiji: Napredak pod ključem(1)), has begun the process of establishing a waste management system and adapting it to the goals and acquis communautaire(2). The key document in Serbia that aims for environmental awareness is called the Waste Management Program of the Republic of Serbia. Followed by the Waste Management Program of the Republic of Serbia, the Regional Waste Management Plan for 2019–2028 has been created and is addressing waste management and establishing a Regional Centre in the city of Novi Sad for Waste Management. Furthermore, the Local Waste Management Plan for the self–government unit of Bački Petrovac has been adopted in May 2021.